PENGARUH FREE CASH FLOW PERUSAHAAN DI TAHAP GROWTH DAN MATURE PADA KEBIJAKAN DIVIDEN - Putri, Putu Anggadewi Darmawan; Putra, I Nyoman Wijana Asmara (E-Jurnal Akuntansi, 2017)
The agency cost could be minimalized by distributing free cash flow to stakeholders in the forms of dividend. This research aimed to test and analyze impacts of firm’s free cash flow on growth and mature stage towards dividend policy. This research used property, real estate and building construction companies which listed in Indonesian Stock Exchange over the period of 2011 to 2015. The sample is obtained by using purposive sampling technique, thus derived 70 observations data which then classified into growth and mature stages. The companies are classified by using sales growth averages for 5 year. The data analysis technique used is simplest linear regression.The results of this research indicates that free cash flow gives positive impact towards dividend policy on both of growth and mature firms, which means that the significance of free cash flows affects the amount of dividend paid.
Keywords: free cash flow, dividend policy, firms life cycle